2020
DOI: 10.1364/optica.384164
|View full text |Cite
|
Sign up to set email alerts
|

Extreme-depth-of-focus imaging with a flat lens

Abstract: A lens performs an approximately one-to-one mapping from the object to the image plane. This mapping in the image plane is maintained within a depth of field (or referred to as depth of focus, if the object is at infinity). This necessitates refocusing of the lens when the images are separated by distances larger than the depth of field. Such refocusing mechanisms can increase the cost, complexity, and weight of imaging systems. Here we show that by judicious design of a multi-level diffractive lens (MDL) it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…These results demonstrate the capability of this structure to effectively focus the THz radiation in a similar fashion to conventional lenses. In addition, the focusing efficiency is calculated by the ratio of the power inside a 3×FWHM region to the power inside the lens area 28 . The result of this calculation is shown in Fig.…”
Section: Experimental Validationmentioning
confidence: 99%
“…These results demonstrate the capability of this structure to effectively focus the THz radiation in a similar fashion to conventional lenses. In addition, the focusing efficiency is calculated by the ratio of the power inside a 3×FWHM region to the power inside the lens area 28 . The result of this calculation is shown in Fig.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Besides, a quite astonishing result revealed in recently published article demonstrated that, an inverse designed 1.8 mmlarge multi-level diffractive lens can achieve diffraction-limit extreme long DOF (≈1200 mm). [55] Obviously, it holds promising potential in applications such as optical imaging with an ultralarge field of view (as demonstrated in the article), in optical lithography, etc. However, it seems not so attractive when applied to LSFM because of the following weaknesses: First, the 3D optical patterns with the non-negligible side lobes (as revealed in Figure S5a-d Second, it may meet with the similar problems encountered by the prism, SQUBIC lens, shifted axicon, and log-aspherical lens when lowered to 1D structure (assume that the inverse designed phase profile is axially symmetric).…”
Section: Comparative Study On 2d Optical Fieldsmentioning
confidence: 97%
“…The high numerical aperture (NA with a value of 1.48) meta-lens (oil immersion) exhibited a 207 nm full width at half maximum (FWHM) of a beam spot with an operational efficiency of 48%, representing one of highest NA of any metalens by that time. Other types of traditional algorithms such as GA and binary search techniques are also demonstrated in, e.g., Pancharatnam-Berry type metalens [76] as well as multi-level diffractive lenses [77][78][79], respectively.…”
Section: Meta-lensmentioning
confidence: 99%